Modern technologies in surgical treatment of combined anorectal pathology and their results - Balytskyy, V.V.; Zakharash, M.P.; Kuryk, O.H. (Medicni Perspektivi, 2022)
Surgery of combined anal and rectal diseases requires an unconventional tactics and methods of treatment of these pathologies, which provide minimal impact on tissues, preventing postoperative complications. The aim of the study was to conduct a comparative evaluation of the effectiveness of new radiosurgical and electrosurgical technologies in the treatment of combined anal and rectal diseases by analyzing the clinical course of the postoperative period and the impact of these energy devices on the morphostructure of operated tissues. The results of treatment of 747 patients with combined anal and rectal diseases divided into four research groups and control group have been analyzed. In the first research group 169 (22,6%) patients with electrosurgery device “ERBE ICC 200” have been operated on in the second research group – 114 (15,3%) patients with electrosurgery device "EFA", in the third research group – 107 (14,3%) patients – with electrosurgery device "KLS Martin" and in the fourth research group – 245 (32,8%) patients with radiosurgery device "Surgitron". The control group consisted of 112 (14,9%) patients operated with a surgical scalpel. After surgery 30 patients from each study group underwent morphological investigation of rectal and anal tissues for measurement of the thickness of thermal impacts on them, which was performed using an eyepiece-micrometer scale. Due to the minimal and insignificant impact on the tissues during application of electrosurgery devices “KLS Martin”, “EFA” and “ERBE ICC 200”, as well as radiosurgery device "Surgitron", there were detected neither scar anal strictures in any of the four study groups, nor scarring deformities of the pararectal areas, which contributed to the cosmetic nature of the combined operations and caused rapid rehabilitation of patients in the study groups. In the control group in 2 (2%) patients the formation of scar anal stricture was diagnosed, which required conservative (1 patient) and operative (1 patient) measures to eliminate them. Using modern radiosurgery and electrosurgery technologies for treatment of combined anal and rectal diseases reduces the operation duration, volume of bleeding and intensity of the postoperative pain. Application of these above technologies prevents the occurance of anal strictures and scar pararectal deformations.